Effects of the wrestling + injury prevention program in freestyle wrestlers: a two-arm randomized controlled trial - Rasoul Bayati; Ali Shamsi Majelan; Hamed Zarei (Journal of Orthopaedic Surgery and Research)
Abstract Background To assess the effectiveness of the Wrestling + injury prevention program on incidence of injuries, neuromuscular mechanisms and dynamic balance of freestyle (FS) wrestler. Methods The participants of this study consisted of FS wrestling players in Qom province (Iran). A total of 80 participants were assigned to this study and using simple and random method with computer divided into experimental (EXP, n = 40) and control (CON, n = 40) groups. The groups were blinded against each other. The follow-up period was one season (6 months). EXP replaced their warm-up by Wrestling + program. CON performed a standard warm-up program. The primary outcome was the injury incidence density (injuries per 1000 h of wrestling exposure), compared between groups by incidence rate ratios (RR). Also, the secondary outcome was neuromuscular mechanisms and dynamic balance. Results The per-protocol analysis showed a reduction of the overall injury incidence density in the EXP group by 58% compared to the CON group. Additionally, within-group analyses revealed significant improvements in neuromuscular mechanisms and dynamic balance for both the EXP and CON groups following 24 weeks of warm-up programs (p < 0.05). Furthermore, between-group comparisons indicated significant differences favoring the EXP group relative to the CON group (p < 0.05). Conclusion The Wrestling + program is effective in reducing injuries among FS wrestlers with overall injuries reduced by 58%. Moreover, the results indicate that the Wrestling + program is more effective than traditional warm-up routines in improving neuromuscular mechanisms and dynamic balance among FS wrestlers. Therefore, it is recommended that coaches use a Wrestling + program to reduce the incidence of injury in FS wrestlers.